HC-MPSOC : plataforma do tipo cluster para sistemas embarcados - Magalhães, Felipe Göhring de (2013)
Multiprocessor System-on-Chip (MPSoC) can be found in virtually all market branches and the design of such systems typically has several restrictions such as chip area used, which hampers. State-of-art MPSoCs uses networks-on-chip as the primary means of communication, and the trend is that systems based on networks intrachip continue to be used for a long time, thanks to greater flexibility in their design and also a high capacity communication. However, such systems also have certain restrictions on its use, such as the location of the tasks that compose it. Mapping and partitioning techiniques seek to solve these problem, or at least decrease it to a non critical point, but are not always successful in this job. In this context, cluster-based architectures emerges as a viable alternative to MPSoCs. Such systems typically have a hybrid architecture in its constitution, using more than one communication medium, thus being able to group elements by questions of "affinity" and still using high-speed communication medias, such as networks-on-chip. Thus, this work introduces the HC-MPSoC, an architecture for cluster-based intrachip systems, which uses buses and networks-on-chip in a joint way, forming groups of elements independently distributed throughout the system. The HellfireOS is also presented, a real time operating system adapted to run on the platform, counting with a full set of drivers throughout a high-level API. All HC-MPSoC modules as well as the HellfireOS modules, and the results obtained using the platform are presented along the text.